Program Metroponik: Edukasi Hidroponik Berbasis Vokasional dalam Pembentukan Jiwa Wirausaha Santri Pondok Madania Yogyakarta - Ahmad Nur Rohim (Universitas Muhammadiyah Surakarta, 2022)
Islamic boarding school is an Islamic education and teaching institution. Islamic intellectual academic curriculum as a provision for independent living, personality, and noble character. Pondok Pesantren Modern Yatim Piatu Dhuafa Madania was established as an orphanage to accommodate orphans with special needs. Efforts to develop hydroponic agriculture as a step in the use of narrow urban land by students are carried out without guidance, direction, and knowledge support so that they are underdeveloped. The author conducts community service in an effort to develop the potential possessed by students. The method used in preparing the design and implementation of educational and coaching activities is an online and offline meeting system starting in August 2020-April 2021. The expected output of the Metroponik Programs that has been prepared is to raise enthusiasm for self-development starting from character, creativity, skills, and later become human resources who survive and are independent without losing religious figures. The results that have been achieved so far are based on indicators of success in increasing agricultural knowledge, providing a space for discussion in the field of agriculture, and the formation of an entrepreneurial spirit. The distribution of knowledge from this program is expected to provide insight in developing their potential to become professional human beings in the field of agriculture and in the future to become agricultural entrepreneurs.